SISTEM PENUNJANG KEPUTUSAN PENENTUAN KELOMPOK PEMINATAN MENGGUNAKAN METODE ANALYTICAL HIERARCHY PROCESS DI SMA NEGERI 1 TUMPANG - Oddie Agung Wardana; Dian Wahyuningsih (Sekolah Tinggi Manajemen Informatika & Komputer PPKIA Pradya Paramita Malang, 2024)
SMA Negeri 1 Tumpang is accredited school A and school that already meet National Education Standards ( NES ) . And mission of SMA Negeri 1 Tumpang include improving academic achievement and create the life skills of graduates and improve academic services for the development of students' potential optimally From the above, the mission of specialization is the most important factor to make the students can learn best at his craft . Analytical Hierarchy Process is a method to use for the selection of specialization in SMAN 1 Tumpang .The results obtained from the analysis of 10 data were tested , 60 % prediction system generates the corresponding specialization , whereas 40 % presiksi system must be determined by the teacher guidance and counseling